Analysis of the functional quality of pavements from texture measurements - Freitas, Elisabete F. (2007)
The surface texture of a pavement, including uneveness, is largely determinant of drivers’safety and comfort. It is undoubtedly a major cause of road traffic accidents all over the world. Statistics show that one million killed and 50 million injured are reported every year by Competent Authorities. The effect of traffic noise has also become a critical public issue. On the road networking the surface characteristics of pavements also contributed to nearly 80-90% of roadway traffic noise. Not only engines or exhaust systems generate noise. The impact of tire-surface at speeds above 50 km/h also needs to be added to prime offenders. Functional requirements such as roadway safety, environmental quality, driving comfort and operating costs in the road network are assessed by indicators whose limits are continuously adjusted. The roadway texture is again a main intervenient. This paper aims at describing the texture indicators that can be used for the assessment of the texture of a pavement from a network point of view, based on profiles acquired at high speeds, including megatexture. First an overview of the concepts related to texture and the effects of texture, including unevenness, on safety, driving comfort, ride quality and environmental quality is given. Then, a case study related to a highly trafficked road in the north of Portugal is presented. This study is the second phase of a broader study that started with the analysis of the structural capacity of that road. In this second phase, a high speed profilometer was used to measure the pavement profile with a sampling rate which is considered to be adequate for the analysis of longitudinal profile, macrotexture and unevenness. Indicators such as the mean profile depth, the IRI and the rutting depth and the corresponding effects were addressed.